Hopanoid-producing bacteria in the Red Sea include the major marine nitrite oxidizers. Issue 6 (12th April 2018) - Kharbush, Jenan J; Thompson, Luke R; Haroon, Mohamed Fauzi; Knight, Rob; Aluwihare, Lihini I
Abstract: Hopanoids, including the extended side chain-containing bacteriohopanepolyols, are bacterial lipids found abundantly in the geological record and across Earth's surface environments. However, the physiological roles of this biomarker remain uncertain, limiting interpretation of their presence in current and past environments. Recent work investigating the diversity and distribution of hopanoid producers in the marine environment implicated low-oxygen regions as important loci of hopanoid production, and data from marine oxygen minimum zones suggested that the dominant hopanoid producers in these environments are nitrite-utilizing organisms, revealing a potential connection between hopanoid production and the marine nitrogen cycle. Here, we use metagenomic data from the Red Sea to investigate the ecology of hopanoid producers in an environmental setting that is biogeochemically distinct from those investigated previously. The distributions of hopanoid production and nitrite oxidation genes in the Red Sea are closely correlated, and the majority of hopanoid producers are taxonomically affiliated with the major marine nitrite oxidizers, Nitrospinae and Nitrospirae . These results suggest that the relationship between hopanoid production and nitrite oxidation is conserved across varying biogeochemical conditions in dark ocean microbial ecosystems. Abstract : This study uses a metagenomic dataset to illuminate the distribution of hopanoid-producing bacteria in the Red Sea.